2008
DOI: 10.1111/j.1365-2958.2008.06229.x
|View full text |Cite
|
Sign up to set email alerts
|

The global, ppGpp‐mediated stringent response to amino acid starvation in Escherichia coli

Abstract: SummaryThe stringent response to amino acid starvation, whereby stable RNA synthesis is curtailed in favour of transcription of amino acid biosynthetic genes, is controlled by the alarmone ppGpp. To elucidate the extent of gene expression effected by ppGpp, we designed an experimental system based on starvation for isoleucine, which could be applied to both wild-type Escherichia coli and the multiauxotrophic relA spoT mutant (ppGpp 0 ). We used microarrays to profile the response to amino acid starvation in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
514
5
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(564 citation statements)
references
References 60 publications
38
514
5
7
Order By: Relevance
“…Recent genome-wide expression studies have reported that at least five and as many as 40 r-protein transcripts decrease following amino acid limitation (22,23). However, as in the earlier studies, conclusions about the mechanistic basis for the decrease in r-protein mRNA levels were constrained by reports that r-protein transcripts had lifetimes of only a few seconds when they were translationally repressed (24,25).…”
mentioning
confidence: 43%
“…Recent genome-wide expression studies have reported that at least five and as many as 40 r-protein transcripts decrease following amino acid limitation (22,23). However, as in the earlier studies, conclusions about the mechanistic basis for the decrease in r-protein mRNA levels were constrained by reports that r-protein transcripts had lifetimes of only a few seconds when they were translationally repressed (24,25).…”
mentioning
confidence: 43%
“…Typical reference choices for northern blot, or quantitative PCR techniques mutatis mutandis , include a ribosomal RNA (rRNA) or another RNA ( rssA , 15 idnT , 16 cysG 16 ) which is not expected to vary in cellular level from sample to sample. However, amino acid starvation triggers a major re-orchestration of the genome-wide transcription pattern 9,17,18 which results in a change in the cellular concentration of most RNA species shortly after the onset of starvation (refs. 18-20 and our manuscript in preparation).…”
Section: The Important Choice Of a Standard For Normalizationmentioning
confidence: 99%
“…However, amino acid starvation triggers a major re-orchestration of the genome-wide transcription pattern 9,17,18 which results in a change in the cellular concentration of most RNA species shortly after the onset of starvation (refs. 18-20 and our manuscript in preparation). Therefore, there is no endogenous reference transcript which is known to be suitable for comparing the cellular levels of tRNA (or any other RNA species) during amino acid starvation to the levels during steady-state growth.…”
Section: The Important Choice Of a Standard For Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimentally induced nutrient limitation represents a strong stimulus 35 that could have triggered the observed response. Accordingly, both the transfer of cytoplasmic markers between cells (Fig.…”
Section: Greenmentioning
confidence: 99%